Capturing the Voices of Children in the Education Health and Care Plans: Are We There Yet? - Palikara, Olympia; Castro, Susana; Gaona, Carolina; Eirinaki, Vasiliki (Frontiers in Education, 2018)
The need for a focus on the voice of children with special educational needs and disabilities (SEND) has received increased recognition internationally both in policy and research. In England, this was emphasized in the new special educational needs framework introduced in 2014. As part of this new policy, children with disabilities and/or additional needs can receive an Education Health and Care (EHC) plan. The EHC plan is a single document that should describe the children’s strengths and needs in a multi-disciplinary and holistic way. Section A of the EHC plan must include the child’s own perspective. In this context there is much need for evidence on the quality of these new plans and in particular on the quality of the depictions of children’s voices. The aim of this study was to address this knowledge gap by analysing the depictions of children’s voices and the process by which these were gathered in 184 EHC plans of children with SEND attending mainstream and special schools in the Greater London area. The content analysis of the section concerning the children’s voices was conducted using the categories of a multi-dimensional classification system, which includes aspects relating to the child herself, but also to her environment and relationships – the International Classification of Functioning, Disability and Health (ICF). The findings revealed high levels of variability in the way the voices of children were captured, including the methods used to ascertain their views. Additionally, the type of school that the child was attending seemed to play a significant role on how his/ her voice was captured, favouring mainstream schools. The findings of the present study provide the first set of evidence-based data concerning the quality of the content of the newly introduced EHC plans and are discussed in light of the implications they have for policy, practice and further research in the area.